ANALISIS MINAT INVESTASI SAHAM PADA MAHASISWA FAKULTAS EKONOMI DAN BINSIS UNIVERSITAS NGURAH RAI - Ni Putu Yuliana Ria Sawitri; Ni Nyoman Sudiyani (Fakultas Ekonomi Universitas Warmadewa, 2023)
Investors from among students are one type of stock investor that has significant growth in the capital market. This shows the high interest in investing in shares for students, especially students in Bali, to invest, but this did not happen at the Faculty of Economics and Business, University of Ngurah Rai. Interest in investing is influenced by various factors including financial literacy and perceived risk, therefore it is very feasible to carry out further research on financial literacy and perceived risk that affect interest in stock investment in students of the Faculty of Economics and Business, University of Ngurah Rai. The formulation of the problem in this study is: how is the simultaneous or partial influence of financial literacy and risk perception on interest in investing in stocks in students of the Faculty of Economics and Business, University of Ngurah Rai? The purpose of this study was to determine the effect simultaneously or partially between financial literacy and risk perception on stock investment interest in students of the Faculty of Economics and Business, University of Ngurah Rai. The number of samples was determined using the slovin formula, namely as many as 88 students of the Faculty of Economics and Business, Ngurah Rai University. Data were analyzed using the classical assumption test, multiple linear regression analysis, determination analysis, simultaneous test (F-test) and partial test (t-test). The results showed that there was a partial and simultaneous positive and significant influence between financial literacy and risk perception on interest in stock investment in students of the Faculty of Economics and Business, Ngurah Rai University.